Axillary Meristem Formation in Rice Requires the WUSCHEL Ortholog TILLERS ABSENT1 . Issue 4 (3rd April 2015) - Tanaka, Wakana; Ohmori, Yoshihiro; Ushijima, Tomokazu; Matsusaka, Hiroaki; Matsushita, Tomonao; Kumamaru, Toshihiro; Kawano, Shigeyuki; Hirano, Hiro-Yuki
Abstract : A WOX gene, TAB1 / WUS, plays a critical role in the initiation of the axillary meristem development in rice. Abstract: Axillary shoot formation is a key determinant of plant architecture. Formation of the axillary shoot is regulated by initiation of the axillary meristem or outgrowth of the axillary bud. Here, we show that rice ( Oryza sativa ) TILLERS ABSENT1 ( TAB1 ; also known as Os WUS ), an ortholog of Arabidopsis thaliana WUS, is required to initiate axillary meristem development. We found that formation of the axillary meristem in rice proceeds via a transient state, which we term the premeristem, characterized by the expression of OSH1, a marker of indeterminate cells in the shoot apical meristem. In the tab1-1 ( wus-1 ) mutant, however, formation of the axillary meristem is arrested at various stages of the premeristem zone, and OSH1 expression is highly reduced. TAB1/WUS is expressed in the premeristem zone, where it shows a partially overlapping pattern with OSH1 . It is likely, therefore, that TAB1 plays an important role in maintaining the premeristem zone and in promoting the formation of the axillary meristem by promoting OSH1 expression. Temporal expression patterns of WUSCHEL-RELATED HOMEOBOX4 ( WOX4 ) indicate that WOX4 is likely to regulate meristem maintenance instead of TAB1 after establishment of the axillary meristem. Lastly, we show that the prophyll, the first leaf in the secondar y axis, is formed from the premeristem zone and not from the axillary meristem.